Family networks and school enrolment: evidence from a randomized social experiment - Manuela Angelucci; Giacomo De Giorgi; Marcos A. Rangel; Imran Rasul (Institute for the Study of Labor (IZA), 2009)
We present evidence on whether and how a household's behavior is influenced by the presence and characteristics of its extended family. Using data from the PROGRESA program in Mexico, we exploit information on the paternal and maternal surnames of heads and spouses in conjunction with the Spanish naming convention to identify the inter and intra generational family links of each household to others in the same village. We then exploit the randomized research design of the PROGRESA evaluation data to identify whether the treatment effects of PROGRESA transfers on secondary school enrolment vary according to the characteristics of extended family. We find PROGRESA only raises secondary enrolment among households that are embedded in a family network. Eligible but isolated households do not respond. The mechanism through which the extended family influences household schooling choices is the redistribution of resources within the family network from eligibles that receive de facto unconditional cash transfers from PROGRESA, towards eligibles on the margin of enrolling children into secondary school.
urn:nbn:de:101:1-200911021620
Keywords: I21; J12; O12; 330; Extended family network; PROGRESA; resource sharing; schooling; Familie; Netzwerk; Bildungsverhalten; Schulauswahl; Ländlicher Raum; Mexiko